2013
DOI: 10.1002/wrcr.20314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aquifer heterogeneity structure and local-scale dispersion on solute concentration uncertainty

Abstract: [1] In this paper, we study the influence of high log-conductivity variance ð 2 Y Þ and localscale dispersion on the first two concentration moments as well as on higher-order moments, skewness, and kurtosis, in a 2-D heterogeneous aquifer. Three different heterogeneity structures are considered, defined with one and the same global isotropic Gaussian variogram. The three structures differ in terms of spatial connectivity patterns at extreme log-conductivity values. Our numerical approach to simulate contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…In the case of the concentration variance, the shape changes from bimodal to unimodal at large enough distances from the source ( Fig. 15 ), as previously observed ( Andricevic, 1998;2008;Schopflocher and Sullivan, 2002;Srzic et al, 2013;Sullivan, 2004 ).…”
Section: The Influence Of Molecular Diffusion On the Concentration Cesupporting
confidence: 82%
See 2 more Smart Citations
“…In the case of the concentration variance, the shape changes from bimodal to unimodal at large enough distances from the source ( Fig. 15 ), as previously observed ( Andricevic, 1998;2008;Schopflocher and Sullivan, 2002;Srzic et al, 2013;Sullivan, 2004 ).…”
Section: The Influence Of Molecular Diffusion On the Concentration Cesupporting
confidence: 82%
“…8 . More results confirming this statement can be found in Srzic et al (2013) and Bellin and Rubin (1994) . Compared to the concentration mean, variance is shown to be sensitive on spatial scale (averaging scale) thus explaining the differences between numerically and analytically obtained concentration variance values shown in Fig.…”
Section: Comparison Of the First Two Concentration Moments Between Ansupporting
confidence: 75%
See 1 more Smart Citation
“…In the other limit, extremely large values of “local‐scale” dispersion dominate any macrodispersive effects, and the macrodispersion equals the local‐scale dispersion. Literature studies have considered finite Pe that range from approximately 10 (Trefry et al, ) to 10,000 (Srzic et al, ), and some (e.g., Beaudoin & De Dreuzy, ; Janković et al, ) have considered no local‐scale dispersion, implying Pe=. Srzic et al () reported that that Pe was important for the time until the plume becomes ergodic (Dagan & Fiori, ; Fiori, ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature studies have considered finite Pe that range from approximately 10 (Trefry et al, ) to 10,000 (Srzic et al, ), and some (e.g., Beaudoin & De Dreuzy, ; Janković et al, ) have considered no local‐scale dispersion, implying Pe=. Srzic et al () reported that that Pe was important for the time until the plume becomes ergodic (Dagan & Fiori, ; Fiori, ). However, for longitudinal macrodispersion, Dentz et al () considered local‐scale dispersion ranging 4 orders of magnitude above that of pure diffusion and σlnK2=1 and found only small sensitivity of the macrodispersion coefficient to the local‐scale dispersion strength.…”
Section: Introductionmentioning
confidence: 99%